GE_GERICHTE P/709/2022 vom 22. Januar 2024 - GE Cour de justice (2024)
PARTIE À LA PROCÉDURE;PERSONNE PROCHE;PARTIE CIVILE;REPRÉSENTATION LÉGALE;QUALITÉ POUR AGIR ET RECOURIR | CPP.382; CPP.115; CPP.116; CPP.117; CPP.122